2022
DOI: 10.1186/s12885-022-10099-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TLN1 as a prognostic biomarker to effect cell proliferation and differentiation in acute myeloid leukemia

Abstract: The protein Talin1 encoded by the TLN1 gene is a focal adhesion-related protein that binds to various cytoskeletal proteins and plays an important role in cell adhesion and movement. Recent studies have shown that it is overexpressed in prostate cancer, liver cancer, and oral squamous cell carcinoma, and is closely related to tumor progression and metastasis. This study integrated bioinformatics and functional analysis to reveal the prognosis and potential functions of TLN1 in AML. The results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…G3 V357 (RNase1) was associated with increased antioxidant gene expression in liver . Recent studies have shown that the overexpression of A0A1S5UZ07 (TLN1) in liver cancer was related to tumor invasion, metastasis, or poor differentiation . Q5JVE7 (F10) is a kind of blood coagulation factors, and several studies have documented the role of blood coagulation factors in mediating liver gene transfer in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…G3 V357 (RNase1) was associated with increased antioxidant gene expression in liver . Recent studies have shown that the overexpression of A0A1S5UZ07 (TLN1) in liver cancer was related to tumor invasion, metastasis, or poor differentiation . Q5JVE7 (F10) is a kind of blood coagulation factors, and several studies have documented the role of blood coagulation factors in mediating liver gene transfer in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…TLN1, locating in focal adhesion, can regulate integrin signaling and promote cancer metastasis [55][56][57][58]. It can affect cell proliferation and differentiation in acute myeloid leukemia [59], define the risk of aggressive oral squamous cell carcinoma [60], and act as a regulator to suppress ovarian serous carcinoma [61]. CALM1 can engage in the formation of calmodulin and regulate proliferation, motility and differentiation through participating in signaling pathways [62].…”
Section: Discussionmentioning
confidence: 99%
“…Another study evaluated the anti-tumor activity of austocystin-D-loaded liposomes (AD-Ls) and suggested that AD-Ls increase the cure efficiency and decrease the side effects on other tissues as shown in animal models of liver cancer ( Li et al, 2013a ). Cui et al, identified TLN1 as a poor-prognostic biomarker in AML and showed that this gene may be related to the resistance of austocystin-D and few other drugs in AML cells ( Cui et al, 2022 ). The other top drugs that were identified include SB-525334, BRD-K34099515, BRD-A02303741, and BRD4132.…”
Section: Discussionmentioning
confidence: 99%